INFLUENCE PROFESSIONAL RESPONSIBILITY AND COMMITMENT TO MOTIVATION AND PERFORMANCE OF EMPLOYEES OF THE PUBLIC WORKS AND SPATIAL PLANNING SERVICE OF SOUTH KALIMANTAN PROVINCE - Elsa Sari; Hary Soegiri (SEAN Institute, 2020)
This research aims to explain the influence of Professional Responsibility, Commitment and Motivation on the Performance of the Public Works and Spatial Planning Office of South Kalimantan Province. This research was conducted at the Office of Public Works and Spatial Planning of South Kalimantan Province and the sample in this study were civil servants. The sampling technique used in this study is the Stratified random sampling method with a total of 105 respondents. The method of collecting data using questionnaires through google form. The data analysis technique used is SPSS to determine the relationship between variables and the SPSS 25 application. The results of this study indicate that professional responsibility has no significant effect on motivation and performance while commitment has an effect on employee motivation and performance and motivation has a positive and significant effect on employee performance.